Marel: from the network of Occupational Medicine consultation centres to the analysis of occupational exposure data - Campo, Giuseppe; Mattioli, Stefano; Cocco, Pierluigi; Cristaudo, Alfonso; Dell'Omo, Marco; Mosconi, Giovanni; Martini, Benedetta; Marinelli, Francesco; Papale, Adriano; Pizzuti, Antonio; Di Francesco, Alessandro; Curti, Stefania (La Medicina del Lavoro, 2018)
Marel (MAlattie e Rischi Emergenti sul Lavoro) project provides, among the main purposes, information on occupational exposure associated to putative work-related diseases. In order to achieve this goal, a network of Occupational Medicine consultation centres has been created. Occupational exposure data are the key information of the Marel system with details that allow analyses about occupational sectors and job-titles. The data recorded in the experimental phase refer to 843 workers visited in five outpatient consultation centres. Women are about 25% of the total and have a lower average age than men, respectively 53 and 59 years. Each worker reports on average two diseases. Among the reported diseases, “Other intervertebral disc disorders” is the most represented group (12.3% out of the total). The homogeneous and systematic collection of information from Occupational Medicine consultation centres can provide a large amount of information useful to design preventive interventions. It also allows to study cases of diseases that, by their nature or their particular relationships with unrecognized professional risk factors, are not yet considered work-related.